2021
DOI: 10.3390/ijerph18041580
|View full text |Cite
|
Sign up to set email alerts
|

Nutshells as Efficient Biosorbents to Remove Cadmium, Lead, and Mercury from Contaminated Solutions

Abstract: The release of potentially toxic elements into the environment, and their effects on aquatic ecosystems still present a real threat. To avoid such contamination, the use of biological sorbents as an alternative to conventional and expensive water remediation techniques has been proposed. The present study evaluated the potential of 0.5 g L−1 of peanut, hazelnut, pistachio, walnut, and almond shells to remove the requisite concentrations of cadmium (Cd), lead (Pb), and mercury (Hg) from contaminated water. Haze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…Furthermore, the hydrated radius of Cd 2+ (0.426 nm) is greater than that of lead Pb 2+ (0.401 nm) (Cheng et al, 2021). All these factors could explain the preferential adsorption of lead compared to that of cadmium on the biosorbent surface (Dias et al, 2021).…”
Section: Preferential Cation Trappingmentioning
confidence: 99%
“…Furthermore, the hydrated radius of Cd 2+ (0.426 nm) is greater than that of lead Pb 2+ (0.401 nm) (Cheng et al, 2021). All these factors could explain the preferential adsorption of lead compared to that of cadmium on the biosorbent surface (Dias et al, 2021).…”
Section: Preferential Cation Trappingmentioning
confidence: 99%
“…Similarly, Xiaotao et al (2016) reported that Cd removal was not affected due to the presence of Hg in the binary system, while Hg was affected significantly. Dias et al (2021) found that the absorptivity of metals by hazelnut, peanut and walnut can be ranked as: Cd>Pb>Hg. Additionally, they found that the transition from single to ternary adsorption system resulted in a decrease in Hg and Cd removal by 14% and 7%, respectively, while Pb showed an insignificant change.…”
Section: Competition Of Metals In a Ternary Systemmentioning
confidence: 99%
“…A biossorção tem vindo a revelar-se como um método eficaz na remoção de elementos tóxicos presentes em soluções, nomeadamente quando estes se encontram em baixas concentrações. Nos últimos anos têm vindo a ser testados diferentes tipos de biossorventes, nomeadamente os constituídos por biomassa de algas, fungos, bactérias, resíduos de plantas e de animais, cascas e diversos outros [8,[11][12][13].…”
Section: Potential Of Macroalgae To Remove Rare Earth Elements From C...unclassified